Popular Evangelicalism in American culture - Kyle, Richard G. (Routledge, 2018)
At home in American culture -- One nation under God -- One market under God -- The millennial nation: two versions -- An Evangelical gospel takes shape -- What can God do for me -- The bigger the better: megachurches and American culture -- Religion can be entertaining: the electronic church -- Evangelicalism embraces the popular culture